Environment and Development: An Economic Approach - Bojö, Jan; Mäler, Karl-Göran; Unemo, Lena (Springer Netherlands, 1990)
This book is a thoroughly revised text based on a report commissioned by the Swedish International Development Authority (SIDA). The financial grant from SIDA which made the work possible is hereby gratefully acknowledged. We gratefully accepted the offer from Kluwer Academic Publishers to revise the text. Hopefully, the text can be of interest to decision-makers, development programme personnel, teachers and the general public interested in how economics can contribute to better environmental decision-making. There are already many books on the market about environmental economics, some of them very good. What is special about this one? We do not claim to have obtained new results, but we have our own way of presenting the subject matter. In particular, we are of the opinion that policy failures are often overlooked as an obstacle to efficient environmental management. Although the main emphasis in this book is on project level analysis, it is essential that such analyses be linked to an understanding of the (dis)incentives for environmental improvements that general economic and particular environmental policies provide. Another essential feature of the book, although this is not unique, is the links provided between theory and empirical illustrations. We hope that this will illustrate to our readers the practical usefulness, but also the difficulties, of applying economics to environmental problems. In principle, this book can be read by anyone interested in the subject matter, without any formal education in economics. However, some background in microeconomic theory makes the reading easier
Keywords: Environmental Economics; Development Economics; Economic Policy; Environmental economics; Development economics; Economic policy; Umweltökonomie; Entwicklungspolitik; Wirtschaftsentwicklung; Umweltschutz